Return to Peyton Place [videorecording (DVD)] - Ferrer, José, 1912-1992; Lynley, Carol, 1942-2019-; Chandler, Jeff, 1918-1961; Parker, Eleanor, 1922-2013; Metalious, Grace (20th Century Fox Home Entertainment, 2004)
"This engaging follow-up to Grace Metalious' best-seller is a study in big-time ambition and small-town narrow-mindedness."--Container.